2019
DOI: 10.48550/arxiv.1908.08150
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brown Measures of Free Circular and Multiplicative Brownian Motions with Self-Adjoint and Unitary Initial Conditions

Abstract: Given a selfadjoint random variable x 0 and a unitary random variable u, different from Haar unitary, free from the free circular Brownian motion c t and the free multiplicative Brownian motion b t , we use the Hamilton-Jacobi method to compute the Brown measures of free circular Brownian motion x 0 + c t and the free multiplicative Brownian motion ub t with probabilistic initial point, extending the recent work [13] by Driver-Hall-Kemp. We find that the supports of the Brown measures are related to the subord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
53
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(59 citation statements)
references
References 23 publications
(52 reference statements)
6
53
0
Order By: Relevance
“…The paper [13] showed that the pushforward of the Brown measure µ s,s of the "standard" free multiplicative Brownian motion b s by a certain map Φ s is equal to the law of the free unitary Brownian motion u s . This result was extended in [23] to relate the Brown measure of ub s to the law of uu s , where u is an arbitrary unitary element freely independent of b s and of u s . The map Φ s in [13,23] is simply the limiting case of the maps Γ τ1,τ2 s with τ 1 = s and τ 2 tending to zero.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…The paper [13] showed that the pushforward of the Brown measure µ s,s of the "standard" free multiplicative Brownian motion b s by a certain map Φ s is equal to the law of the free unitary Brownian motion u s . This result was extended in [23] to relate the Brown measure of ub s to the law of uu s , where u is an arbitrary unitary element freely independent of b s and of u s . The map Φ s in [13,23] is simply the limiting case of the maps Γ τ1,τ2 s with τ 1 = s and τ 2 tending to zero.…”
mentioning
confidence: 98%
“…This result was extended in [23] to relate the Brown measure of ub s to the law of uu s , where u is an arbitrary unitary element freely independent of b s and of u s . The map Φ s in [13,23] is simply the limiting case of the maps Γ τ1,τ2 s with τ 1 = s and τ 2 tending to zero. We see, then, that the map Φ s is simply a limiting case of the whole family of maps Γ τ1,τ2 s relating all the Brown measures µ s,τ with s fixed and τ varying.…”
mentioning
confidence: 98%
See 3 more Smart Citations